Clinical and Angiographic Outcomes After Stent-Assisted Coiling of Cerebral Aneurysms With Laser-Cut and Braided Stents: A Comparative Analysis of the Literatures - Zhang, Longhui; Chen, Xiheng; Dong, Linggen; Liu, Peng; Jia, Luqiong; Zhang, Yisen; Lv, Ming (Frontiers in Neurology, 2021)
Introduction: Stent-assisted coiling (SAC) plays an important role in endovascular treatment of intracranial aneurysms (IAs). This comparative analysis examines the safety and efficacy of SAC in general and compares clinical and angiographic outcomes between laser-cut stents and braided stents. Methods: Relevant English-language studies were identified via a PubMed search for published articles regarding outcomes of SAC using laser-cut stents and braided stents published from 2015 to 2020. Data from 56 studies that met our inclusion criteria were pooled and statistically compared. Results: A total of 4,373 patients harboring with 4,540 IAs were included. Patients were divided into two groups on the basis of stent type: laser-cut stents (2,076 aneurysms in 1991 patients; mean follow-up, 12.99 months) and braided stents (2,464 aneurysms in 2382 patients; mean follow-up, 18.41 months). Overall, the rates of successful stent deployment, thromboembolic events, stent stenosis, periprocedural intracranial hemorrhage, permanent morbidity, mortality, and recanalization were 97.72, 4.72, 2.87, 1.51, 2.14, 1.16, and 6.06%, respectively. Laser-cut stents were associated with a significantly higher rate of successful deployment (p = 0.003) and significantly lower rate of periprocedural intracranial hemorrhage (p = 0.048). Braided stents were associated with a significantly lower rate of permanent morbidity (p = 0.015). Conclusion: SAC of IAs using laser-cut stents or braided stents was effective and safe. Rates of thromboembolic events, stent stenosis, mortality, and recanalization were comparable between the stent types. Braided stents were associated with lower permanent morbidity while laser-cut stents were associated with more favorable rates of successful deployment and periprocedural intracranial hemorrhage.